PROFIL DAN KARAKTERISTIK PENANGKAPAN IKAN OLEH NELAYAN ARTISANAL DI WPP-713 UNTUK PERTIMBANGAN ADAPTASI PERUBAHAN IKLIM - Puji Rahmadi (Jurnal Harpodon Borneo, 2018)
Artisanal fisheries playing an important rule to preserve the economic stability of tradisional fishermans. This type of fisheries are very vulnerable to climate change since the habitat of target fishes are very narrow, area limited, and usually those area are sencitive to the  physical changes of water colomn. One area which is artisanal fisheries can be found broundly and in a huge number was in Fisheries Management Area of 713 (WPP 713) (PERMEN KP No. 18 Tahun 2014). In order to identify the profiles and characters of artisanal fisheries in WPP 713, sampling have been conducted at Paotere fisheries port and Mamuju fisheries port. The results shows that artisanal fisheries in WPP 713 has a character of using several various fishing gear according to their targeted fishes which is also fickle. In other hand, they also has a habit to move their fishing ground from one place to anothers. This profile are a potential to be developed into an adaptation strategy to facing climate change effect of global warming. However the government’s participation become very important on this situation as the authority that managed the fishing gears type, recommending the location and period of fishing ground in order to pursue the sustainable fisheries optimally.